Introduction of Remote Sensing and Geographic Information System Concepts for Tsunami Disaster Mitigation at SMK N 1 Tanjungsari - Sari, Dewi Novita; Danardono, D; Wibowo, Afif Ari; Priyono, uswaji Dwi; Anna, Alif Noor (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
A natural disaster is a phenomenon that can occur anywhere and anytime. It creates risk and danger that affects the lives of living things. Tsunami is one of the natural disaster which is difficult to predict. The limited understanding of people who live in tsunami-prone areas needs to be improved. Remote sensing and Geographic Information Systems (GIS) are branches of geographical sciences that can be used for tsunami disaster mitigation. As an effort to introduce the concepts of Remote Sensing and GIS, a community service activity was conducted for senior high school students. This community service aims to provide students with an understanding and skills in tsunami mitigation in their surrounding areas. This can foster interest in the field of geography and provide insight into the importance of tsunami disaster management. The partner of this activity is SMK N 1 Tanjungsari, located in the coastal area of Gunungidul, Yogyakarta. This location was chosen because it has a high level of risk of tsunami. The capacity building phase was conducted through mitigation training. The results obtained that knowledge about disaster and self-defense adaptation skills from students increased after the training.